Cold water immersion settings for reducing muscle tissue temperature: a linear dose-response relationship - Vromans, B. A.; Thorpe, R. T.; Viroux, P. J.; Tiemessen, I. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Although cold water immersion (CWI) is widely accepted and integrated as a recovery modality in sports practice, questions regarding its proposed working mechanisms remain. This study systematically reviews the existing literature on one the proposed mechanisms of CWI, its effect on muscle tissue temperature, and subsequently tries to identify a dose-response relationship in order to describe an optimal dose. EVIDENCE ACQUISITION: A systematic literature search (PubMed and Sport Discus) was conducted in October 2017. Dose-response relationships were analyzed using linear regression while controlling for possible confounders (muscle measurement depth and immersion position). EVIDENCE SYNTHESIS: A total of 10 studies, with a total of 104 participants, were included utilizing 26 different CWI protocols. Muscle tissue temperatures were reduced significantly by 24 CWI protocols. A significant, relationship with a medium effect size (r=0.51) was identified between muscle tissue temperature and CWI. The most optimal dose-response relationship, with a large effect size, (r=0.87) was described for CWI protocols using full-body immersion at a measurement depth of 30 mm (y = 4.051 x + 0.535). CONCLUSIONS: CWI can decrease muscle tissue temperature significantly if a minimum CWI dose of 1.1 is applied, corresponding with an immersion of 11 minutes with a water temperature of 10 °C.